1995
DOI: 10.1046/j.1365-2648.1995.22030528.x
|View full text |Cite
|
Sign up to set email alerts
|

Busy doing nothing: activity and interaction levels amongst differing populations of elderly patients

Abstract: This paper considers the activity and interaction levels amongst three differing populations of elderly patients (long-stay, short-stay and respite). It begins with a consideration of the literature on staff-patient interactions in care environments for elderly patients, highlighting the virtual absence of preplanned, purposeful activity. Data are then presented which suggest that, despite the emphasis nurses place on communicating with their patients, many patients continue to spend most of their time inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 34 publications
2
84
1
Order By: Relevance
“…Armstrong-Esther et al [58], Waters [59], Edberg et al [60] and Nolan et al [61] use molar observations, such as physical activity and non-interactive behaviour. While Davies [62], Salmon [63] and Thomas [64] use specifically defined verbal communication categories, such as explanation and jokes or puns.…”
Section: Quantitative Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Armstrong-Esther et al [58], Waters [59], Edberg et al [60] and Nolan et al [61] use molar observations, such as physical activity and non-interactive behaviour. While Davies [62], Salmon [63] and Thomas [64] use specifically defined verbal communication categories, such as explanation and jokes or puns.…”
Section: Quantitative Researchmentioning
confidence: 99%
“…For instance, the studies in elderly care [59,[61][62][63] or in the intensive care [73,74] do not offer specific clues for instrument development in oncology care. Studies directed at the occurrence of verbal and nonverbal behaviour, rather than the content of communication [71,72], neither offer guidelines for instrument development in cancer nursing (right-most column in Table 3).…”
Section: Observation Instruments Applicable To Research Into Nurse-pamentioning
confidence: 99%
“…5 In contrast, high levels of engagement in both individually (eg, reading) and socially based activities (eg, group activities) have been associated with decreased agitation and psychotropic medications, increased resident quality of life 8e10 and satisfaction among resident families. 11 In the first study available in the field conducted in the United States, Gottesman and Bourestom 4 reported that around 56% of the 1144 NH residents included were inactive; around 20 years later, Nolan et al 12 conducted an observational study on 49 residents in 2 different continuing care units in North Wales (United Kingdom), documenting that around 70% of them spent their time in passive activities. More recently, Edvardsson et al, 13 using a cross-sectional study, included 1266 residents from 156 residential elderly care units in Sweden, reporting that the prevalence of inactivity among the residents in the previous week had ranged from 38% to 87% of the time.…”
mentioning
confidence: 99%
“…The activity sessions involved interactive storytelling, crafts, cooking, entertainment, guest speakers, indoor gardening, hair styling, and light exercising. Such activities are often referred to as social and diversional activities (Houston, McKee, & March, 1998;Nolan, Grant, & Nolan, 1995) and are known to improve patients' stimulation, self-esteem, and enjoyment. About 10 minutes before the activity, the activities director, a volunteer, and some of the nurses brought willing patients to the room.…”
Section: Setting and Participantsmentioning
confidence: 99%